PROYEKSI RATA-RATA PENDAPATAN NELAYAN TRADISIONAL DESA BUNGABALI KECAMATAN PANTAR TIMUR BULAN MARET 2023 DENGAN MENGGUNAKAN MODEL EKSPONENSIAL - Melki Imamastri Puling Tang (MathVisioN, 2022)
The income of traditional fishermen in Bungabali village, Pantar Timur sub-district, based on research data, will be used to project the income of traditional fishermen using the exponential model. When the researcher analyzes the data, the researcher will compare the data of several years that already exist with the projected data. From the comparison results, it turns out that the projected data is close to the actual data. Therefore, the projection is close to the actual data, so the exponential model can be used to project the income of traditional fishermen in 2022 to March 2023. Researchers project the income of traditional fishermen in Bungabali village, Pantar Timur sub-district every month, starting from January 2022 until the month of January 2022. March 2023. After that, researchers will clearly get the results of the projected income of fishermen in Bungabali village, Pantar Timur sub-district, precisely in March 2023. Projected average amount of income (not deducted by operating costs) or gross income for traditional fishermen in Bungabalik village, Pantar district East Alor district in March 2023 as much as 1473,302 thousand rupiah or Rp. 1,473,302 or approximately Rp. 1,473,000. This income analysis has not yet calculated expenses or operational costs. The fishermen are very dependent on the results of fishing. The economic condition of the household is still concerning, which will have an impact on many conditions, including the level of education of the fishermen's children. The results of interviews by researchers with fishermen stated that on average it was difficult for fishermen to take care of their children to the level of education due to unstable income. Keywords: average income, exponential model.